Sedation for gastrointestinal endoscopy with the application of target-controlled infusion - Chang, Yi-Ting; Tsai, Tzung-Chieh; Hsu, Huan; Chen, Yung-Ming; Chi, Kuang-Piao; Peng, Shih-Yen (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: A majority of esophagogastroduodenoscopy (EGD) and colonoscopy procedures are performed under sedation, with the intravenous administration of a hypnotic agent combined with an opioid analgesic agent. The goal of our study was to establish the quality and plausibility of target-controlled infusion (TCI) as a sedation mechanism for upper and lower gastrointestinal (GI) endoscopies. Materials and Methods: A randomized, single-blinded, controlled clinical trial was arranged in a local community hospital. In total, 100 adult outpatients scheduled for upper and lower GI endoscopies were included and randomly allocated to a control group (n=50) and a TCI group (n=50). The sedation quality was assessed using the simplified quality of an anesthesia scoring system. Categorical parameters were compared using Pearson’s chi-square test. Continuous parameters that were normally distributed were further compared using Student’s t-test, and the others were compared using the Mann–Whitney test. Results: The significantly lower anesthesia quality score in the TCI group (12.2 vs. 12.7) indicated that the anesthesia quality was better in this group. Conclusion: This study showed that sedation using TCI for GI endoscopy provided safe and effective sedation and was associated with a better sedation quality. We believe that TCI can be used to provide routine sedation for patients receiving GI endoscopy.